Nietypowa przytarczowa lokalizacja neowaskularyzacji podsiatkówkowej – opis przypadków - Figurska, Małgorzata; Wierzbowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Choroidal neovascularization (CNV) is one of the main reasons for sight loss in adults. CNV located at the border of the optic disc or adherent atrophy is described as peripapillary choroidal neovascularisation (PPCNV). The aim of the work is to present a course of changes and the effects of treatment with intravitreal ranibizumab injections for peripapillary subretinal neovascularization, its consequences and accompanying other CNV foci in two patients. The diagnosis and monitoring of the therapeutic effects were based on the results of fluorescein angiography and OCT. In a 53-year-old female patient three injections of ranibizumab at a dose of 0.05 mg were administered according to a saturation regimen. Visual improvement of 5 lines on an ETDRS board (25 letters) was obtained, as well as withdrawal of the subretinal fluid from the area of the macula in OCT and limitation of the peripapillary exudate visible in 12 months follow-up angiography. In a 70-year-old female patient bilateral development of symmetric peripapillary CNV foci was observed accompanied by a occult CNV focus in the left eye macula. Spontaneous CNV limitation without macular lesions was visible in the right eye. Intravitreal ranibizumab injections were given into the left eye. A 12 months follow-up revealed vision stabilisation in both eyes at the baseline level. Conclusions: Intravitreal injections can be used in the treatment of atypical extramacular CNV, responsible for secondary damage to the fovea. Ranibizumab, a non-selective VEGF-A inhibitor, allows the elimination of changes in the central retina, closure or significant limitation of the exudates and vision improvement. Spontaneous limitation of lesions may also be frequently expected in the eyes with peripapillary CNV foci.